Lifestyle habits associated with nocturnal urination frequency: The Nagahama study. Issue 8 (4th September 2019) - Tabara, Yasuharu; Matsumoto, Takeshi; Murase, Kimihiko; Setoh, Kazuya; Kawaguchi, Takahisa; Nagashima, Shunsuke; Funada, Satoshi; Kosugi, Shinji; Hirai, Toyohiro; Nakayama, Takeo; Wakamura, Tomoko; Chin, Kazuo; et al.
Abstract: Background: Nocturia is a risk factor for poor quality of life and increased mortality. This study was aimed to clarifying dietary habits, eating behaviors, and sleep characteristics associated with nocturia to identify modifiable lifestyle factors for nocturia. Methods: This cross‐sectional study included 5683 community residents (64.5 ± 7.7 years old). The frequency of nocturnal urination was recorded for 1 week using a sleep diary. The frequency of food intake, unfavorable eating behaviors, and sleep characteristics that may have influence on salt intake and wasting were obtained using a structured questionnaire. Results: The frequency of nocturnal urination was increased with age (β = .312, P < .001). Other basic factors associated with the frequency were the male sex (β = .090), hypertension (β = .038), sleep apnea (β = .030), B‐type natriuretic peptide level (β = .089), and spot urine sodium excretion (β = −.058). Dietary factors independently associated with nocturnal urination frequency were coffee (≥1 time/day: β = −.059, P < .001) and green vegetable consumption (≥1 time/week: β = −.042, P = .001), whereas habitual intake of dairy products, miso soup, and alcohol were not associated with urination frequency. Later bedtime was inversely associated with nocturnal urination frequency independent of sleep duration (before 23:00: β = −.096; before 24:00: β = −.225; after midnight: β = −.240; all P < .001). Conclusion: Coffee and green vegetable consumption and later bedtime but not sleep duration are lifestyle factors associated with nocturnal urination frequency.